SUPERVISORY CONTROL AND DATA ACQUISITION FOR A ROBOTIC ARM VIA GRAFCET - BANIRAM, SYAHRIL IZWAN (Universiti Teknologi PETRONAS, 2007)
The aim of this report is to focus on the basic programming structure of PLC and its application in industry. This report emphasizes understanding of Grafcet language through the basic knowledge of ladder diagram method. A robotic arm will be programmed to do some specific tasks. The main programming language to be used would be Grafcet. Notably, since the language is relatively new, several aspects of the programming method would be required to be explored. Specific software named AUTOMGEN is available and it provides some features inclusive of pneumatic/electrical/hydraulic simulation module for any automation application and SCADA 3D process simulation. Programming of the Grafcet would be conducted by using State-by-State (SS) approach and classic truth table simplification. The truth table is to be constructed based on the timing diagram of the motions of the robotic arm. Previous work on the robotic arm controlled via PLC programming using ladder diagram had shown a successful achievement. In this project, Grafcet language is opted to be used for programming becauseof its concurrency for both simplicity and easy understanding. It would expect that a clear description of programming using Grafcet could be achieved and the general features of programming a PLC could be understood.